Model Pengelolaan Sampah Berbasis Komunitas Melalui Program Zero Waste di Masjid Salman ITB - Fazri, Azri Syahrul; Aulia, Dhine Putri; Anugrah, Asyeu; Sidik, Mohamad Dindin Hamam (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to analyze a community-based waste management model through the zero-waste program at Salman Mosque ITB as an effort to address social and ecological issues caused by waste generation. The zero-waste approach is crucial because the growing population is not accompanied by adequate awareness and mindset in managing waste, resulting in the overcapacity of Final Disposal Sites (TPA). This research employs a qualitative method using field studies and literature reviews. The data were collected through observation, interviews, documentation, and literature studies from books, scientific articles, and relevant online sources. The findings reveal that the Salman Environment Rangers (Savior) community, empowered at Salman Mosque ITB, plays a central role in educating the public about waste sorting and management, as well as implementing a waste donation program to reduce the burden on TPA. The implications of this study demonstrate that a community-based approach through the zero-waste program can foster responsible consumption and production patterns and contribute to achieving the Sustainable Development Goals (SDGs). The originality of this research lies in its direct observation of community-based waste management practices in a mosque setting, which remains underexplored in the context of zero waste in Indonesia.